(untitled) (Journal of Parents and Teachers, 2012)
An investment in quality is implicit in popular education. Further from the Access, popular sectors have the right to get a good education. It is no true that a bad education is better than no education. The best possible education for the ones who are in the worst conditions is better and necessary.